Sustainable Production of Concrete Using Waste Water - Bansal, Shivani (My University, 2019)
Availability of clean water and disposal of wastewater has become a major environment issue. One common solution to both the problems is the recycled use of water. Here the reuse potential of waste effluent from different sources in mixing and curing of concrete has been investigated. In this study, wastewater from four different sources was collected and used in mixing as well as curing of concrete. One of the main objectives of this study is to evaluate utilization of wastewater in mixing and curing of concrete. Wastewater was collected from sewage treatment plant of Verka industry (food-based industry), aluminium industry containing acid, aluminium industry without acid and wastewater from Thapar sewage treatment plant. For control samples, normal tap water was taken. The concrete mixes were casted and cured with the same water whether it is wastewater or tap water (control mix). Performance of concrete mixes was judged by evaluating compressive strength, split tensile strength, water absorption and corrosion current density. The microstructure of the mixes was analyzed by Scanning electron microscopy (SEM) and XRD. Properties of different waters were also compared. It was observed that compressive strength of concrete mixed and cured with wastewater was less as compared to the compressive strength of control mix. In addition, water absorption was greater for these wastewatersamples as compared to control samples that were mixed and cured using tap water.
Keywords: waste water; sustainable construction; concrete